The Challenging in silico Description of Carbon Monoxide Oxidation as Catalyzed by Molybdenum-Copper CO Dehydrogenase - Rovaletti, Anna; Bruschi, Maurizio; Moro, Giorgio; Cosentino, Ugo; Greco, Claudio (Frontiers in Chemistry, 2019)
Carbon monoxide (CO) is a highly toxic gas to many living organisms. However, some microorganisms are able to use this molecule as the sole source of carbon and energy. Soil bacteria such as the aerobic Oligotropha carboxidovorans are responsible for the annual removal of about 2x108 tons of CO from the atmosphere. Detoxification through oxidation of CO to CO2 is enabled by the MoCu-dependent CO-dehydrogenase enzyme (MoCu-CODH) which—differently from other enzyme classes with similar function—retains its catalytic activity in the presence of atmospheric O2. In the last few years, targeted advancements have been described in the field of bioengineering and biomimetics, which is functional for future technological exploitation of the catalytic properties of MoCu-CODH and for the reproduction of its reactivity in synthetic complexes. Notably, a growing interest for the quantum chemical investigation of this enzyme has recently also emerged. This mini-review compiles the current knowledge of the MoCu-CODH catalytic cycle, with a specific focus on the outcomes of theoretical studies on this enzyme class. Rather controversial aspects from different theoretical studies will be highlighted, thus illustrating the challenges posed by this system as far as the application of density functional theory and hybrid quantum-classical methods are concerned.